1998
DOI: 10.1021/om9708283
|View full text |Cite
|
Sign up to set email alerts
|

Metallacyclopentane Formation:  A Deactivation Pathway for a Tungsten(VI) Alkylidene Complex in Olefin Metathesis Reactions

Abstract: W(NPh)[o-(Me3SiN)2C6H4](CH2CMe3)2, 2h, is quantitatively converted to a new metallacyclopentane complex, W(CH2CH2CH2CH2)(NPh)[o-(Me3SiN)2C6H4], 4, upon the addition of ethylene at T > 70 °C. The complex W(CH2CH2CH2CH2)(NPh)[o-(Me3SiN)2C6H4], 4, was also formed by the transmetalation reaction of W(NPh)[o-(Me3SiN)2C6H4](Cl)2 with the corresponding Grignard reagent, BrMg(CH2)4MgBr, and also when W(NPh)[o-(Me3SiN)2C6H4](PMe3)(C(H)t-Bu), 3, reacts with ethylene. Mechanistic studies suggest that 2h and 3 react with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…The formation of propene byproducts and the observation of a metallacyclopentane intermediate is reminiscent of the well documented (for molecular complexes) formation of metallacyclopentane intermediates from M­(IV) olefin adducts (M = Ta, Mo, W) and their ring contraction to form carbene species (Figure F) . This suggests that the formation of the carbene active sites in our material occurs by a similar mechanism.…”
Section: Resultssupporting
confidence: 75%
“…The formation of propene byproducts and the observation of a metallacyclopentane intermediate is reminiscent of the well documented (for molecular complexes) formation of metallacyclopentane intermediates from M­(IV) olefin adducts (M = Ta, Mo, W) and their ring contraction to form carbene species (Figure F) . This suggests that the formation of the carbene active sites in our material occurs by a similar mechanism.…”
Section: Resultssupporting
confidence: 75%
“…The C1 C2 bond distance of the coordinated ethylene molecule is 1.41 Å, indicating a significant back-donation from the metal center to the π* orbital of ethylene. 41 In the presence of 3 equiv of B(C 6 F 5 ) 3 , the reaction of 2a and 13 C-dilabeled ethylene yields the py-B(C 6 F 5 ) 3 adduct, 3a-C 2 H 4 , and a small amount of the metallacyclopentane 4a (Scheme 4) at room temperature. Heating the reaction mixture to 50 °C leads to complete conversion of 3a-C 2 H 4 and removal of most of the coordinated pyridine from W centers to give py-B(C 6 F 5 ) 3 (ca.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“… , 3a-C 2 H 4 can be isolated by recrystallization in toluene at −40 °C, and its structure is confirmed by single-crystal X-ray diffraction studies. The C1C2 bond distance of the coordinated ethylene molecule is 1.41 Å, indicating a significant back-donation from the metal center to the π* orbital of ethylene . In the presence of 3 equiv of B­(C 6 F 5 ) 3 , the reaction of 2a and 13 C-dilabeled ethylene yields the py-B­(C 6 F 5 ) 3 adduct, 3a-C 2 H 4 , and a small amount of the metallacyclopentane 4a (Scheme ) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Reference is made to the isolation by Boncella et al of an imido-tungstanacyclopentane complex, which whilst confirming the existence of metallacyclic species for tungsten, was the deactivation by-product from metathesis. 25 This, coupled with the ability to isolate and characterise this species suggests that it is kinetically inert, resisting breakdown of the metallacycle and hence perhaps not a This journal is © The Royal Society of Chemistry 2010 catalytically important intermediate. Nonetheless, computational studies have suggested that a metallacyclic pathway may be energetically feasible for tungsten-imido based catalysts.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%